Analisis Pemahaman Konsep Siswa pada Operasi Hitung Pembagian dan Perkalian pada Bilangan Bulat - Unaenah, Een; Sartika, Devi; Syurgaini, Joya; Ramadanti, Saskia (ARZUSIN, 2022)
The study aims to identify understanding concepts in students in understanding the division and multiplication of operations calculate integer Numbers and identify the difficulties students experience in completing integer operations on the division and multiplication and factors influencing the difficulties to occur. The study was conducted by taking a few samples of the elementary school student of the vi class and interviewing one of the vi grade elementary school teachers.the instruments in the study are tests and interviews with studies that indicate that students got misconception on the story of the division and multiplication story and were less understanding how the system of division of the lower Numbers was operating. The cause of students' lack of understanding in understanding the story and the concept of the division of Numbers is that students have difficulty understanding the concept of division, difficulty in understanding the concept of partition, difficulty in understanding the basic fact of division. As for the factors that affected the difficulty of learning the division between them; Cognitive factors, interest factors, study time attention and parent factor and teacher factor.